Prevalence and risk factors of viral diseases in broiler farms contracted to multifactorial respiratory syndrome - Fallah Mehrabadi, MH; Moluoki, A; Bashashati, M; Rabiee, MH; Ghalyanchilangeroudi, A; Shoushtari, A; Motamed, N (Journal of the Hellenic Veterinary Medical Society, 2025)
Newcastle, Influenza H9N2 and Infectious Bronchitis are the major respiratory diseases in broiler poultry farming in Iran. This study aims to investigate prevalence and risk factors of these viral diseases in commercial broiler chicken farms contracted to multi-factorial respiratory syndrome in Iran. In this cross-sectional study, 157 affected commercial broiler chicken farms in Iran were sampled during 2017 to 2019. Samples were examined for avian influenza H9N2, Newcastle, and infectious bronchitis by performing reverse transcription polymerase chain reaction. Possible risk factors for the occurrence of viral diseases were investigated by comparing the mean and frequency of the factors, as well as performing univariate and multivariate regression analysis. Highest frequency of investigated viral diseases was due to Newcastle disease with 98 cases (62.43%, CI 95%= 54.35-70.01). Frequency of avian influenza H9N2 and infectious bronchitis was respectively 74 cases (47.13%, CI 95%= 39.13-55.25) and 22 cases (14.1%, CI 95%= 8.99-20.44). Flock age (Odd Ratio: 2.65, P value: 0.030) and first week mortality (Odd Ratio: 10.12, P value: 0.014) respectively had significant effect on occurrence of influenza H9N2 and co-infection of influenza H9N2. Control strategies must be implemented on the broiler farms. Continuous monitoring of the farms and investigation of the the farm vaccination programs every year are among the necessary control strategies measures and must be implemented.